The transformation of Islamic windows in conventional banks into independent Islamic banks - Rima, Berarma; Adem, Hadidi; Manel, Lamri (The International tax journal, 2025)
This study aims to analyze the phenomenon of transforming Islamic windows in conventional banks into independent Islamic banks, focusing on the economic, regulatory, and Sharia-driven motivations behind this transformation. The research also explores the challenges facing this process, such as capital requirements, establishing an independent Sharia identity, and dealing with customers and regulatory authorities. The study adopts a descriptive and analytical approach based on a review of literature and practical experiences in several Islamic countries. The findings indicate that the shift toward independence enhances trust in Islamic banking, promotes financial inclusion, and reduces the overlap between conventional and Islamic activities within banking institutions.